Revision of the fungus-growing ant genera Mycetophylax Emery and Paramycetophylax Kusnezov rev. stat., and description of Kalathomyrmex n. gen. (Formicidae: Myrmicinae: Attini) - Klingenberg, Christiana; Brandão, C. Roberto F. (Zootaxa, 2009)
Based on the morphology of workers, gynes and males, we revise the taxonomy of nominal taxa traditionally included by authors in the fungus-growing ant genus Mycetophylax. Our results indicate that Mycetophylax Emery (Myrmicocrypta brittoni Wheeler, 1907, type species, by designation of Emery, 1913; junior synonym of Cyphomyrmex conformis Mayr, 1884 by Kempf, 1962) includes M. conformis, M. simplex (Emery, 1888), and M. morschi (Emery, 1888) new combination (formerly in Cyphomyrmex), with several synonymies. Mycetophylax bruchi (Santschi, 1916) does not belong to the same genus and is diagnosed, in addition to other characters, by a psammophore arising at the anterior margin of the clypeus. For this species we are resurrecting from synonymy Paramycetophylax Kusnezov, 1956 (Mycetophylax bruchi as type species, by original designation, with M. cristulatus as its new synonym). Myrmicocrypta emeryi Forel, 1907 is the only attine in which females lack the median clypeal seta and have the antennal insertion areas very much enlarged and anteriorly produced, with the psammophore setae arising from the middle of the clypeus and not at its anterior margin as in Paramycetophylax. Notwithstanding its inclusion in Mycetophylax by recent authors, it is here recognized as belonging to a hitherto undescribed, thus far monotypic genus, Kalathomyrmex new genus (Myrmicocrypta emeryi as its type species, here designated). We redescribe workers, gynes and males of all species in the